2012
DOI: 10.1136/acupmed-2011-010114
|View full text |Cite
|
Sign up to set email alerts
|

Electroacupuncture Prevents Ovariectomy-Induced Osteoporosis in Rats: A Randomised Controlled Trial

Abstract: Background Electroacupuncture (EA) treatment has been shown to increase bone mineral density (BMD) in ovariectomised (OVX) rats; however, the underlying mechanisms remain unclear. Objective To systematically evaluate the effects of EA on OVX rats and the Wnt/β-catenin signalling pathway. Methods Three-month-old female Sprague-Dawley rats were randomly divided into three different groups (n=10 each): sham operated control (sham operated), ovariectomy (OVX) and ovariectomy with EA treatment (OVX+EA). Rats in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
1
2

Year Published

2014
2014
2018
2018

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 29 publications
(21 reference statements)
1
19
1
2
Order By: Relevance
“…In the present study, DEXA, mCT, and biomechanical results confirmed the successful establishment of OVX rat model of osteoporosis. These results are consistent with those of our previous studies which showed irreversible changes in BMD, bone microarchitechture, and strength after ovariectomy [Zhou et al, 2012a[Zhou et al, ,b, 2013[Zhou et al, , 2014. The relatively higher proportion of cortical bone in the femur as compared to that in the lumbar vertebral body may account for the sitespecific discrepancy in BMD and bone strength.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In the present study, DEXA, mCT, and biomechanical results confirmed the successful establishment of OVX rat model of osteoporosis. These results are consistent with those of our previous studies which showed irreversible changes in BMD, bone microarchitechture, and strength after ovariectomy [Zhou et al, 2012a[Zhou et al, ,b, 2013[Zhou et al, , 2014. The relatively higher proportion of cortical bone in the femur as compared to that in the lumbar vertebral body may account for the sitespecific discrepancy in BMD and bone strength.…”
Section: Discussionsupporting
confidence: 93%
“…Animals were housed in an environmentally controlled laboratory (12 h light/dark cycle; relative humidity: 55 ± 5%; temperature 24 ± 2 °C) with free access to water and food. Rats underwent bilateral ovariectomy or sham surgery after 1 week of acclimatization, as described elsewhere [Zhou et al, ,, , ]. Figure illustrates the experimental study design.…”
Section: Methodsmentioning
confidence: 99%
“…First, the mechanisms underlying the synergistic efficacy of IBN + PEMF are not fully understood, and further research is needed. Secondly, although osteoporosis can be successfully established using 3‐month‐old rats (matured but young) [Sehmisch et al, ; Yang et al, ; Zhou et al, ,, , ], growth‐dependent effects may have influenced the results.…”
Section: Discussionmentioning
confidence: 99%
“…Animals were housed in stainless‐steel wire cages under standard laboratory conditions (12 h light/dark cycle, relative humidity of 55 ± 5%, 24 ± 2 °C) with free access to water and food. After 1 week of acclimatization, all rats were subjected to either bilateral ovariectomy or sham surgery, as we previously described [Zhou et al, ,, , ].…”
Section: Methodsmentioning
confidence: 99%
“…To evaluate the bone strength, the three-point bending examination for the left femur was performed by the AG-IS (Shimadzu, Japan) biomechanical testing system according to our previous description [24]. The femurs were slowly thawed and warmed to room temperature.…”
Section: Biomechanical Examinationmentioning
confidence: 99%